Rape phosphatide concentrate in the technologies of surfactants production by the Actinobacteria - N. Koretska (Ukrainian Food Journal, 2015)
Introduction. Due to the fact that the production of microbial surfactants is limited by the low yield of end products and high cost of processes, the actual task is to optimize and reduce the cost of the technology of biosurfactants synthesis. One of the solutions of this problem is to use the industrial wastes, including rape phosphatide concentrate (PC). Materials and methods. Hexadecane and rape phosphatide concentrate (2%) were used as a carbon source in a nutrient medium for the cultivation of bacteria. Lipids were extracted from a cell mass and supernatant by the mixture of chloroform-methanol 2:1. The qualitative analysis of metabolites was performed by a thin layer chromatography. Results and discussion. The peculiarities of synthesis of biosurfactants by strains G. rubripertincta UCM Aс-122 and R. erythropolis Au-1 during the growth on the nutrient media with rape phosphatide concentrate as a carbon source was studied. Quantity of biomass was 9.4 – 10.1 g/l, exopoly mers –8.9-9.5 g/l and the content of cellbound trehalose lipids was 1.37 – 2.26 g/l; whereas the content of exogenous trehalose lipids –metabolites of R. erythropolis Au-1 was 2.95 g/l. It was found that the addition of trehalose lipids (0.01 g/l) to the nutrient medium caused the increase of biomass on 14.6 –17.0 % and cell-bound lipids on 13.9 –15.5 %. Conclusions. Rape phosphatide concentrate is economically viable carbon source in the technologies of surfactant production by Actinobacteria. Its use promotes an increasing of exogenous surfactants strain R. erythropolisAu-1 in 3-fold compared with cultivation on nutrient medium with hexadecane. Trehalose lipids show a stimulating effect on growth and synthesis of biosurfactants by strains of G. rubripertincta UCM Ac-122 and R. erythropolisAu-1.